Event DAS-444Ø6-6 soybean grown in Brazil is compositionally equivalent to non-transgenic soybean. Issue 2 (2nd April 2016) - Fast, Brandon J.; Galan, Maria P.; Schafer, Ariane C.
ABSTRACT: Soybean event DAS-444Ø6-6 is tolerant to the herbicides 2, 4-D, glyphosate, and glufosinate. An investigation of potential unintended adverse compositional changes in a genetically modified crop is required to meet government regulatory requirements in various geographies. A study to meet these requirements in Brazil was completed demonstrating compositional equivalency between DAS-444Ø6-6 and non-transgenic soybean. This study supplements the extensive literature supporting transgenesis as less disruptive of crop composition compared with traditional breeding methods.